The Use of TAT Peptide-Functionalized Graphene as a Highly Nuclear-Targeting Carrier System for Suppression of Choroidal Melanoma - Shan, Suyan (Int J Mol Sci, 2019)
Tumorous metastasis is a difficult challenge to resolve for researchers and for clinicians. Targeted delivery of antitumor drugs towards tumor cells’ nuclei can be a practical approach to resolving this issue. This work describes an efficient nuclear-targeting delivery system prepared from trans-activating transcriptional activator (TAT) peptide-functionalized graphene nanocarriers. The TAT peptide, originally observed in a human immunodeficiency virus 1 (HIV-1), was incorporated with graphene via an edge-functionalized ball-milling method developed by the author’s research group. High tumor-targeting capability of the resulting nanocarrier was realized by the strong affinity between TAT and the nuclei of cancer cells, along with the enhanced permeability and retention (EPR) effect of two-dimensional graphene nanosheets. Subsequently, a common antitumor drug, mitomycin C (MMC), was covalently linked to the TAT-functionalized graphene (TG) to form a nuclear-targeted nanodrug MMC-TG. The presence of nanomaterials inside the nuclei of ocular choroidal melanoma (OCM-1) cells was shown using transmission electron microscopy (TEM) and confocal laser scanning microscopy. In vitro results from a Transwell co-culture system showed that most of the MMC-TG nanodrugs were delivered in a targeted manner to the tumorous OCM-1 cells, while a very small amount of MMC-TG was delivered in a non-targeted manner to normal human retinal pigment epithelial (ARPE-19) cells. TEM results further confirmed that apoptosis of OCM-1 cells was started from the lysis of nuclear substances, followed by the disappearance of nuclear membrane and cytoplasm. This suggests that the as-synthesized MMC-TG is a promising nuclear-target nanodrugfor resolution of tumorous metastasis issues at the headstream.